The relationship between diet and the risk of diabetes mellitus in elementary school children grades 4-6 at Sdn Tasikmadu 1 Malang - Oktafiani, Khoirun Nisa; Astuti, Erlina Suci (Institute of Computer Science (IOCS), 2025)
The prevalence of Diabetes Mellitus (DM) among children in Indonesia has shown a significant increase in recent years. The rise in type 2 diabetes is influenced not only by genetic factors but also by unhealthy lifestyles, particularly poor dietary habits. This study aimed to examine the relationship between diet and the risk of diabetes mellitus among elementary school students in grades 4–6 at SDN Tasikmadu 1 Malang. This quantitative research used a cross-sectional design and was conducted in May 2025, involving a sample of 100 students. Data were analyzed using the Chi-square test. The results showed that among children with unhealthy diets, 27 students (46.6%) had a high risk of diabetes, while among those with moderate diets, 18 students (42.9%) had a low risk. Statistical tests showed a significant association between dietary patterns and diabetes risk (χ² = 7.544; p = 0.023), with a linear-by-linear association (χ² = 7.135; p = 0.008). These findings indicate that the less healthy a child’s diet is, the higher their risk of developing early symptoms of diabetes. In conclusion, there is a significant relationship between dietary patterns and the risk of Diabetes Mellitus among elementary school children.